2021
DOI: 10.1200/jco.20.03288
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt Lymphoma International Prognostic Index

Abstract: PURPOSE Burkitt lymphoma (BL) has unique biology and clinical course but lacks a standardized prognostic model. We developed and validated a novel prognostic index specific for BL to aid risk stratification, interpretation of clinical trials, and targeted development of novel treatment approaches. METHODS We derived the BL International Prognostic Index (BL-IPI) from a real-world data set of adult patients with BL treated with immunochemotherapy in the United States between 2009 and 2018, identifying candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…prognostic indices? [114][115][116] has been conducted in richer countries. The exclusion of poorer countries from BL research is ironic given that Denis Burkitt's epoch-making report was based on cases seen in Africa [12].…”
Section: Discussionmentioning
confidence: 99%
“…prognostic indices? [114][115][116] has been conducted in richer countries. The exclusion of poorer countries from BL research is ironic given that Denis Burkitt's epoch-making report was based on cases seen in Africa [12].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostication of survival outcomes in BL, especially with the respect to mutation status of a single predictor gene or gene panel, is under-studied compared to the association of BL survival with treatment 23 or clinical factors 24 . To determine the clinical relevance of newly discovered genetic subgroups in BL and their dominant features, we stratified patients using the most common mutations representative of the three BL-predominant subgroups, revealing significant associations between mutation status and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Total metabolic tumour volume was also investigated in Burkitt lymphoma (BL), in which most patients have advanced stage disease and/or bulky lesions at diagnosis. 80 A retrospective study of 65 BL patients found that using the SUV41% method, tMTV and TLG were independent prognostic factors for PFS and OS in multivariable analyses. 81 The optimal tMTV cut-off by ROC analysis was 231 ml.…”
Section: Mantle Cell Lymphoma (Mcl) and Burkitt Lymphomamentioning
confidence: 99%